Gus’ Transformational Leadership to Realize Individual Consideration In The Ministry of Ungentlemanly Warfare Movie - Nurdin, Dewi Syifanaya Firadausy; Pasopati, Rommel Utungga (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study examines how transformational leadership is portrayed, namely the idea of individual consideration, as exemplified by Gus March-Phillips in Guy Ritchie's film The Ministry of Ungentlemanly Warfare. The movie, which is set during World War II, emphasizes how Gus's leadership promotes friendship, providing personal attention, mentoring and coaching, respecting different needs and learning styles, and creating a supportive environment. The research demonstrates Gus's capacity to coach, give individualized attention, and foster an inclusive atmosphere that improves his team's relationships and mission achievement through a qualitative examination of significant conversations and situations. The results show how individual consideration and regard for individual needs, which are hallmarks of transformational leadership, can improve team cohesiveness and personal development.